Strategies for research participant engagement: A synthetic review and conceptual framework. (August 2021) - Wong, Charlene A; Song, William B; Jiao, Megan; O'Brien, Emily; Ubel, Peter; Wang, Gary; Scales, Charles D
Background: Research participant engagement, which we define as recruitment and retention in clinical trials, is a costly and challenging issue in clinical research. Research teams have leveraged a variety of strategies to increase research participant engagement in clinical trials, although a framework and evidence for effective participant engagement strategies are lacking. We (1) developed a novel conceptual framework for strategies used to recruit and retain participants in clinical trials based on their underlying behavioral principles and (2) categorized empirically tested recruitment and retention strategies in this novel framework. Methods: We conducted a synthetic analysis of interventions tested in studies from two Cochrane reviews on clinical trial recruitment and retention, which included studies from 1986 to 2015. We developed a conceptual framework of behavioral strategies for increasing research participant engagement using deductive and inductive approaches with the studies included in the Cochrane reviews. Reviewed interventions were then categorized using this framework. We examined the results of reviewed interventions and categorized the effects on clinical trial recruitment and retention as significantly positive, null, or significantly negative; summary statistics are presented for the frequency and effects of each behavioral strategy type. Results: We analyzed 141 unique interventions across 96 studies: 91 interventions targeted clinical trial research participant recruitment and 50 targeted retention. Our framework included 14 behavioral strategies to improve research participant engagement grouped into four general approaches: changing attitudes by appealing to social motivators, changing attitudes by targeting individual psychology, reducing barriers and cognitive burdens, and providing incentives . The majority of interventions (54%) aimed to reduce barriers or cognitive burdens, with improving comprehension (27%) as the most common specific strategy identified. For recruitment, the most common behavioral strategies tested were building legitimacy or trust (38%) and framing risks and benefits (32%), while financial or material incentives (32%) and reducing financial, time, and social barriers (32%) were most common for retention interventions. Among interventions tested in randomized controlled trials, 51% had a null effect on research participant engagement, and 30% had a statistically significant positive effect. Discussion: Clinical researchers have tested a wide range of interventions that leverage distinct behavioral strategies to achieve improved research participant recruitment and retention. Common behavioral strategies include building legitimacy or trust between research teams and participants, as well as improving participant comprehension of trial objectives and procedures. The high frequency of null effects among tested interventions suggests challenges in selecting the optimal interventions for increasing research participant engagement, although the proposed behavioral strategy categories can serve as a conceptual framework for developing and testing future interventions.